# algebra 1

posted by .

can someone please help me solve the question and explain to me and also show me specifically what to do step by step???

Q: what is the standard form of
Y-8=2(x+2)?

• algebra 1 -

MISTAKE:

its actually y-8=2(x+3)

• algebra 1 -

A. 2x+y=14
B. y=2x+14
C. 2x-y=-14
D. y-2x=11

• algebra 1 -

most texts use these definitions:

y intercept - slope form : y = mx + b
standard form: Ax + By = C
general form : Ax + By + C = 0

so you want the x and y terms on one side, the constant on the other side

y - 8 = 2(x+3)
y - 8 = 2x + 6
2x + 6 = y - 8
2x - y = -14 , looks like C

• algebra 1 -

Ax +By = C

y-8 = 2x +6
y-8-6 =2x + 6 -6
y-14 = 2x
y-y -14 = 2x -y
-14 = 2x-y

C

## Similar Questions

1. ### Pre-Algebra [urgent!]

I can't find the solution to this problem; can someone please show me how to solve it step-by-step?
2. ### Algebra help

f(x)=x^3-4x^2-x+4 How do I find the x-intercept for this?
3. ### Algebra 2

can someone show me how to do it step by step please! Use a graph and table to solve each system. check your answer {y+x=5 {3x-5y=-1
4. ### chemistry

I don't understand this zwitterion form . Here is the question. write the zwitterion form of the amino acid cysteins shown in the follwing figure. If the pI for cysteine is 5.1 at what pH will the zwitterions be the predominant form?
5. ### Algebra

Can someone explain to be how to put (x/ (x^2-4)) in another form... please show step by step thank you!
6. ### Algebra

Can someone explain to be how to put (x/ (x^2-4)) in another form... please show step by step thank you!
7. ### Algebra

How to solve d(d^-2)^-9? Please show and explain step-by-step.
8. ### Algebra 1--Step-by-Step

Can someone show me how to solve these step-by-step?
9. ### Algebra 1 (Step-by-Step)

Will someone explain how to solve this? Write each equation in standard form. Solve by using the Quadratic Formula. 1. -7 = x^2
10. ### Math

I need help solving the problem not the answer. (Multiple Choice) The steps below show the incomplete solution to find the value of x for the equation 7x + 8 − 3x = −6 + 10: Step 1: 7x + 8 − 3x = −6 + 10 Step 2: 7x + 8 − …

More Similar Questions